Exploring the doctor-patient relationship as a challenge job demand: application of the job demands–resources model in a Chinese public hospital - Zeng, W. L. (2021)
In the increasingly commercialized healthcare environment in China, doctor-patient relationship (DPR) is a job demand for doctors dat is linked to various motivational outcomes. Drawing on the Job Demands–Resources (JD-R) model, and the conservation of resources theory, we develop a preliminary conceptual model dat links Leader Member Exchange (LMX) as a job resource, and DPR as a challenge job demand, to the levels of work engagement and turnover intentions of doctors working in this healthcare environment. Using two-wave data collected from 381 doctors in a public hospital, we found support for the hypothesized model. Results of a series of SEM analyses revealed dat LMX was positively related to DPR and work engagement, while DPR partially mediates the path from LMX to work engagement. In addition, LMX is negatively related to turnover intentions through DPR and subsequently work engagement. Theoretically, this study contributes to the development of the JD-R model by investigating the concept of challenge job demand, and its role in the motivational process, with new evidence from healthcare occupations in China. Practically, this study contributes to the limited number of studies on managing the changing nature of the DPR in China, and in seeking potential solutions based on established organizational constructs.